A new species of Neofilchneria (Plecoptera: Perlodidae) from China, with supplementary information on N. wanglanga Chen, 2019 - Zhang, Yao; Li, Wenliang; Li, Weihai (Zootaxa, 2024)
A new species of the perlodid genus Neofilchneria Zwick, 1973, N. cheni sp. nov. from Hubei Province of central China, is described, illustrated, and compared with related congeners. Neofilchneria wanglanga Chen, 2019 is newly recorded from Yunnan Province. The hitherto unknown aedeagus of N. wanglanga is described for the first time.